The breakthrough and the future: CD20 chimeric antigen receptor T‐cell therapy for hematologic malignancies. Issue 1 (5th October 2022) - Tan Su Yin, Elaine; Hu, Yong Xian; Huang, He
Abstract: Chimeric antigen receptors (CAR) T‐cell therapy is one of the most effective treatments in curing hematologic malignancies. Besides the four CD19 CAR T‐cells therapy recently approved by the US Food and Drug Administration (FDA), CD20 CAR T‐cell therapy is now another effective treatment option for relapsed or refractory non‐Hodgkin lymphoma (NHL). CD20 CAR T‐cell infusion has achieved remarkable clinical outcomes in patients with B‐cell malignancies. This review will cover the current situations, advantages, limitations, prospects, and application of CD20 CAR T‐cell therapy.